A lung cancer mouse model system based on an inbred C3H strain: Ultrasound imaging, pathological analysis, and proteomic biomarker identification - Ulayatul Kustiati; Wahyu Tri Widayati; Dwi Liliek Kusindarta; Dwi Aris Agung Nugrahaningsih; Dinda Aliffia; Wilda Bunga Tina Sanjaya; Hevi Wihadmadyatami (Veterinary World)
Background and Aim: Lung cancer remains a leading cause of global mortality, necessitating robust animal models for research into its mechanisms and therapeutic options. This study aimed to develop and validate a novel lung cancer mouse model using the inbred C3H strain through intraperitoneal (I.P) injection of benzo(a)pyrene, offering insights into hematology, pathology, imaging, and proteomic biomarkers.